Cover Image, Volume 115, Number 12, December 2018. Issue 12 (11th November 2018) - Jo, Migyeong; Hwang, Bora; Yoon, Hyun Woung; Jung, Sang Taek
Abstract : The cover image is based on the Article Escherichia coli inner membrane display system for high‐throughput screening of dimeric proteins by Migyeong Jo et al., DOI:10.1002/bit.26826 . Illustration Credit: Bora Hwang, Kookmin University.